Secondary hematological malignancies following breast cancer treatment - Soley Bayraktar; Maricer P. Escalon (Frontiers Media S.A., 2011)
Breast cancer (BC) incidence has increased among women in most Western countries. Concurrently, the survival time of BC patients has increased with 5-year survival rates reaching 80-90%. Secondary hematological malignancies (SHM) following BC treatment are an issue of concern to clinicians and also to patients and their families. However, therapy-induced leukemia after BC is an underemphasized clinical problem. In this review,we will focus on the incidences and patterns of occurrence ofSHM in patients with BC. We will address risk factors for the development of SHM and we will explore how secondary hematological malignancies impact the survival of BC patients.